The Process of Application of Female-Language Criteria in Two Selected Books, The Last Sunday and Shina’s Daughter, Looking at Sarah Mills' Linguistic Approach - Mojgan Jafari; Soheila Mosavi Sirjani; Abdolhossein Farzad (Matn/Pizhūhī-i Adabī, 2021)
Holy defense is a part of our country's history, and a fair look at this historic period is realized when it’s studied through the minds of all those who were involved. The books of women's war memories, both quantitatively and qualitatively, still have a lot to do with men's diary books. Here, the frequency of the use of twenty components of feminine effects of language, expressed by experts or understood by the author, was evaluated by emphasizing on existence of women's style in their writings, reviewing two selected books of women's memories in national festivals that were selected with ten years time distance, “The last Sunday” and “Shina’s daughter”, and looking at Sarah Mills' linguistic approach at levels of linguistic structure, thought, and content structure. These components can contribute to the process of developing a theoretical critique of women’s works, especially in the war memories field. In the process of these components' application over ten years, usage of feminine vocabulary in the linguistic structure (Lexical) has been significantly enhanced in “Shina's daughter” versus “The last Sunday” and referring to the religious and national doctrines (in the structure of thought and content) has been significantly decreased. Pointing to the color and material of objects in “Shina's daughter” is modestly reduced, but the use of a weak and supportive tone is increased. The rest criteria were not changed significantly. These changes can be influenced by the cultural, political, and social circumstances of the society or the author's individual circumstances.